1999
DOI: 10.1023/a:1006123819675
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of vitamin D3 analogs and paclitaxel on the growth of MCF-7 breast cancer cells in vivo

Abstract: Vitamin D3 analogs and paclitaxel (Taxol) are able to inhibit the in vitro growth of a variety of malignant cells including breast cancer cells. These two compounds decrease growth by different mechanisms and they have nonoverlapping toxicities. We examined the abilities of three vitamin D3 compounds to inhibit growth of a human mammary cancer (MCF-7) in BNX triple immunodeficient mice either alone or with Taxol. Vitamin D3 analogs were 1,25(OH)2D3 (code name, Compound C), 1,25(OH)2-16-ene-23-yne-19-nor-26,27-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…Stage IVC patients had a significant clinical benefit, but without improved survival [32]. In other studies, co-treatment with 1,25(OH) 2 D 3 and paclitaxel resulted in enhanced anti-tumor activity in models of prostate cancer and breast cancer [33,34]. A clinical pharmacokinetic study of the combination treatment even suggested attenuation of the 1,25(OH) 2 D 3 -induced-hypercalcemia in combination with paclitaxel [35].…”
Section: Discussionmentioning
confidence: 99%
“…Stage IVC patients had a significant clinical benefit, but without improved survival [32]. In other studies, co-treatment with 1,25(OH) 2 D 3 and paclitaxel resulted in enhanced anti-tumor activity in models of prostate cancer and breast cancer [33,34]. A clinical pharmacokinetic study of the combination treatment even suggested attenuation of the 1,25(OH) 2 D 3 -induced-hypercalcemia in combination with paclitaxel [35].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, at the higher dose, EB1089 determined tumor regression. In addition, on one hand, experimental evidence showed that the combination of EB1089 with cytotoxic agents and/or ionizing radiation resulted in additive antitumor effects on breast cancer tumor cells either in vitro or in vivo (Demasters et al, 2006;Koshizuka et al, 1999;Sundaram et al, 2003;Valrance et al, 2007). On the other hand, Oades et al (2002) showed that EB1089 also inhibited the growth of prostate adenocarcinoma in the Dunning prostate model and in athymic nude mice transplanted with LNCaP.…”
Section: Eb1089 (Seocalcitol)mentioning
confidence: 99%
“…showed at least additive effects. In an in vivo breast cancer mice model, for example, additive effects on tumor growth inhibition were observed when the 1,25(OH) 2 D analog EB1089 was combined with taxol [47]. The use of 1,25(OH) 2 D or its analogs in humans has yet been very limited.…”
Section: Intervention Trials With Vitamin 125(oh) 2 D or Vitamin D mentioning
confidence: 99%